2012
DOI: 10.1111/j.1753-0407.2012.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antihypertensive effect of a polyphenol‐rich fraction of Thymelaea hirsuta L. in a model of neonatal streptozotocin‐diabetic and NG‐nitro‐l‐arginine methyl ester‐hypertensive rats

Abstract: Background: The present study examined the effect of the polyphenol-rich fraction from Thymelaea hirsuta (PRF-Th) in a rat model of streptozotocin (STZ)-diabetes and nitric oxide (NO)-deficient hypertension. Methods: Diabetes was induced by a single dose of STZ (90 mg ⁄ kg, i.p.). To induce NO-deficient hypertension, rats were treated with the NO synthase inhibitor N G -nitro-l-arginine methyl ester; l-NAME; 30 mg ⁄ kg per day, p.o. for 3 weeks. The effects of 21 days treatment with 80 mg ⁄ kg per day PRF-Th i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Thymelaea hirsuta contains sterols (cholesterol, campesterol, β‐sitosterol, β‐sitosterol‐ β‐stigmasterol), coumarins (daphnoretin, daphnin, daphnetin, daphnetin‐glucoside, umbelliferone, scopoletin and esculetin), terpenes (lupeol, phytol, β‐amyrine, betulin, erythrodiol, and lanosterol), a flavone (2‐vicenin), the flavonol tiliroside (3‐p‐coumaroylglucosylkaempferol), tannins, an aliphatic alcohol (C12H22O), a lactone (C19H18O6); long chain alkanes (27‐31 carbons), long chain alcohols (22, 24, 26, 28 carbons) and 5,12‐dihydroxy‐6,7‐epoxy‐resiniferonol …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thymelaea hirsuta contains sterols (cholesterol, campesterol, β‐sitosterol, β‐sitosterol‐ β‐stigmasterol), coumarins (daphnoretin, daphnin, daphnetin, daphnetin‐glucoside, umbelliferone, scopoletin and esculetin), terpenes (lupeol, phytol, β‐amyrine, betulin, erythrodiol, and lanosterol), a flavone (2‐vicenin), the flavonol tiliroside (3‐p‐coumaroylglucosylkaempferol), tannins, an aliphatic alcohol (C12H22O), a lactone (C19H18O6); long chain alkanes (27‐31 carbons), long chain alcohols (22, 24, 26, 28 carbons) and 5,12‐dihydroxy‐6,7‐epoxy‐resiniferonol …”
Section: Discussionmentioning
confidence: 99%
“…aliphatic alcohol (C12H22O), a lactone (C19H18O6); long chain alkanes (27-31 carbons), long chain alcohols (22,24,26,28 carbons) and 5,12-dihydroxy-6,7-epoxyresiniferonol. 7,22 Previous studies have shown that T. hirsuta is rich in polyphenols 9 and essential oil. 11 Therefore, the polyphenols and essential oil compounds are most likely responsible for the antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…antidirehyde and purgative and in the treatment of influenza 1-2,5-6,10, [13][14][15][16][17] . In M'Sila region, T. hirsuta is recommended by herbalists for the treatment of human diseases (Leishmanicide, dewormer and eczema) 18 .…”
Section: T Microphylla T Hirsuta T Lythroidesmentioning
confidence: 99%